Influence of pH value on chromate-free conversion coating for magnesium alloys - 翁文凭 陈琦 张慧 钟皓 闫蕴琪 (Transactions of Nonferrous Metals Society of China, 2006)
Many factors were found to have effects on the conversion coatings for AZ31 alloy, alloy the most important one in producing high quality conversion coatings is found to be the control of the pH value. The influence of pH value on the conversion coating including color, thickness, adhesion and surface morphology was studied. The performance of conversion coating was examined by cross cut test, SEM method and salt immersion. The results show that the variation ofpH value causes surface treatment process unstably. The conversion coating can obtain as pH value ranging from 3.0 to 5.0, while it presents dark, thick and bad adhesion under lower pH value. The conversion coatings have good combination of thickness and adhesion when pH value ranging from 4.0 to 4.5, and it exhibits a good corrosion resistance.